ARTIFICIAL INTELLIGENCE (AI) DALAM SISTEM AKUNTANSI: TINJAUAN ETIS TERHADAP PRIVASI DATA DAN TRANSPARANSI LAPORAN KEUANGAN - Abrar, Lutfi Andi (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine in depth the ethical issues related to data privacy and transparency of financial reports in the application of Artificial Intelligence (AI) to accounting systems. Using a literature review method of 20 relevant scientific articles, this study examines how AI, although able to improve efficiency and accuracy in financial reporting, also presents serious risks to data security and clarity of the decision-making process. The results of the study indicate that the use of AI in accounting can strengthen accuracy detection and increase reporting speed, but on the other hand opens up the potential for privacy violations due to weak data protection and the use of non-transparent algorithms (black-box). Discussion of the importance of integrating professional ethical principles such as integrity, objectivity, and responsibility in the use of AI, as well as the need to increase digital literacy among accountants. This study also highlights the urgency of special regulations and algorithm audits as a form of technological accountability. Therefore, the use of AI in accounting must be accompanied by strengthening regulations, increasing human resource capacity, and collaboration between stakeholders to ensure the use of this technology is ethical, safe, and responsible.